A case report of mevalonate kinase deficiency in a 14-month-old female with fevers and lower extremity weakness - Tiziana Coppola; Bradford Becken; Heather Van Mater; Marie Theresa McDonald; Gabriela Maradiaga Panayotti (BMC, 2019)
Abstract Background This case follows a 14-month-old female, who despite multiple presentations to several physicians, continued to have recurrent febrile episodes with gross motor delay. Her case revealed an often missed diagnosis of Mevalonate Kinase Deficiency, that now has an FDA approved treatment that both reduces recurrence and produces remission. Case presentation A 14-month-old female with a history of gross motor delay, frequent Upper Respiratory Tract infections, and otitis media presented to an urgent care for inconsolability and refusal to bear weight on her right leg. She had recently been treated with amoxicillin for acute otitis media and had developed a diffuse maculopapular rash, without any associated respiratory or gastrointestinal distress that persisted beyond cessation of the antibiotics. The patient presented multiple times to an urgent care over the subsequent week for fussiness, fever, anorexia, lymphadenopathy, with labs concerning for worsening anemia and elevated inflammatory markers. Subsequently, the patient was admitted to the hospital for suspected osteomyelitis versus oncologic process. X-Ray imaging of the patient's lower extremities showed osseous abnormalities inconsistent with infection. A metabolic work-up showed elevated urine mevalonic acid, and follow-up genetic testing was positive for mutations in both copies of her mevalonate kinase gene. This led to the diagnosis of MKD. Conclusions Often, episodic presentations require multiple perspectives to reveal the underlying cause. This case illustrates how apparent simple febrile episodes has the potential for more complexity upon further evaluation.